2023
DOI: 10.1021/acs.molpharmaceut.3c00009
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Membrane Wrapped Nanoparticles for the Delivery of a Bcl-2 Inhibitor to Triple-Negative Breast Cancer

Abstract: Overexpression of the antiapoptotic protein B-cell lymphoma 2 (Bcl-2) is correlated with poor survival outcomes in triple-negative breast cancer (TNBC), making Bcl-2 inhibition a promising strategy to treat this aggressive disease. Unfortunately, Bcl-2 inhibitors developed to date have limited clinical success against solid tumors, owing to poor bioavailability, insufficient tumor delivery, and off-target toxicity. To circumvent these problems, we loaded the Bcl-2 inhibitor ABT-737 in poly(lacticco-glycolic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Many anticancer drugs increase the expression of caspase 3, Bax, and p53, which kills cancer cells (LeBlanc et al 2002). In this instance, we were able to trigger apoptosis in cancer cells by upregulating Bax and caspases and downregulating BCL2 expression (Scully et al 2023). The consistent changes in the expression of Bax and BCL2 revealed that the Bax/BCL2 signaling pathway might be a common mechanism to inhibit tumor growth, which is a viable direction for creating methods for treating various malignancies.…”
Section: Discussionmentioning
confidence: 88%
“…Many anticancer drugs increase the expression of caspase 3, Bax, and p53, which kills cancer cells (LeBlanc et al 2002). In this instance, we were able to trigger apoptosis in cancer cells by upregulating Bax and caspases and downregulating BCL2 expression (Scully et al 2023). The consistent changes in the expression of Bax and BCL2 revealed that the Bax/BCL2 signaling pathway might be a common mechanism to inhibit tumor growth, which is a viable direction for creating methods for treating various malignancies.…”
Section: Discussionmentioning
confidence: 88%
“…M any different cell types have been used for nanoparticle membrane coating (Table 1). Notably, a range of cancer lines has been used, including cervical and ovarian cancers [21][22][23][24], multiple myeloma [25], melanoma [12,[26][27][28][29][30][31][32], leukemia [23,[33][34][35][36][37][38][39][40][41][42][43][44], breast cancer [6,37,40,[45][46][47][48][49][50][51][52][53][54][55][56], neuroblastoma [79], colon carcinoma [23,57], head and neck squamous cell carcinoma [58][59][60][61], lung cancer…”
Section: Membrane Donor Cellsmentioning
confidence: 99%
“…Most researchers employed hypotonic lysis in their studies [6,12,19,[21][22][23][24][25][26][27][29][30][31][32][33][34][35][36]38,39,[41][42][43][44][45][48][49][50][51][54][55][56][57][58][60][61][62][63][64][65][66][67][69][70][71][72][73][74][75][76][77]79,81,…”
Section: Hypotonic Lysismentioning
confidence: 99%
See 2 more Smart Citations